Modelling of parametric kinetic ion-acoustic instability in helicon discharge - Olshansky, V.V. (Вопросы атомной науки и техники, 2015)
A computer simulation of the development of the parametric kinetic ion-acoustic instability is carried out for the helicon discharge conditions by the "particle in cell" method. Linear and nonlinear stages of the ion-acoustic instability and turbulence are investigated for the typical parameters of the helicon plasma. It is shown that the high efficiency of the helicon plasma sources can relate to development of both short and long wavelength kinetic ion-acoustic parametric instabilities and the turbulent heating of electrons and ions caused by the ion-acoustic turbulence can be one of the dominant mechanisms of the pumping wave energy absorption in the helicon plasma.